Myostatin knockout drives browning of white adipose tissue through activating the AMPK‐PGC1α‐Fndc5 pathway in muscle - Tizhong Shan; Xinrong Liang; Pengpeng Bi; Shihuan Kuang (2013)
Myostatin (Mstn) is predominantly expressed in skeletal muscles and plays important roles in regulating muscle growth and development, as well as fat deposition. Mstn-knockout (Mstn(-/-)) mice exhibit increased muscle mass due to both hypertrophy and hyperplasia, and leaner body composition due to reduced fat mass. Here, we show that white adipose tissue (WAT) of Mstn(-/-) develops characteristics of brown adipose tissue (BAT) with dramatically increased expression of BAT signature genes, including Ucp1 and Pgc1α, and beige adipocyte markers Tmem26 and CD137. Strikingly, the observed browning phenotype is non-cell autonomous and is instead driven by the newly defined myokine irisin (Fndc5) secreted from Mstn(-/-) skeletal muscle. Within the muscle, Mstn(-/-) leads to increased expression of AMPK and its phosphorylation, which subsequently activates PGC1α and Fndc5. Together, our study defines a paradigm of muscle-fat crosstalk mediated by Fndc5, which is up-regulated and secreted from muscle to induce beige cell markers and the browning of WAT in Mstn(-/-) mice. These results suggest that targeting muscle Mstn and its downstream signaling represents a therapeutic approach to treat obesity and type 2 diabetes.